Legal consciousness and legal culture in the era of total digitalization: Theoretical-methodological and legal-technical problems - Baranov, Pavel P.; Mamychev, Alexey Y.; Dremliuga, Roman I.; Miroshnichenko, Olga I. (Linguistics and Culture Review, 2021)
The paper analyses the change in ideas about law in the digitalization era. Noting the insufficient theoretical substantiation of attempts to impose on modern law any special characteristics arising from the widespread development of digital technologies, the authors admit that in the era of virtual reality, the laws of the digital virtual world begin to actively compete with the laws of nature. This entails a slight decrease in the role of law as a traditional regulator of social relationships. However, according to the authors, one should not artificially diminish the role of law even in the era of digitalization. In this regard, the paper discusses the main trends in the study of legal digitalization processes. The first trend is due to the need to promptly respond by legal means to the emergence of new areas of legal regulation caused by the widespread use of digital information technologies. The second trend assumes the expansion and rethinking of the subject and object of legal science within the context that new digital "participants" of legal relations born due to intelligent human activity emerge.